New Media Futures - Faltesek, Daniel (Open textbook library., 2019)
This book is intended for use in a large introductory class in new media in a program that covers the “full-stack” including critical/cultural studies, media management, diffusion of innovation, and synthetic media production. The first half of this basic sequence covered new media and democracy, finance, intellectual property law, basic games, and transmedia. The second half of the sequence covers many topics related to aesthetics, design, technology, and methodology. To that end, this book needed to be written so that it would be helpful for many different professors and trajectories of study. This book is in neither engineering, social science, nor the humanities, but also all of those. At the same time, this is a program in the Communication Studies and Media Studies traditions of the United States and that texture will come across.